2012
DOI: 10.1016/j.neuropharm.2011.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human MFG-E8 attenuates cerebral ischemic injury: Its role in anti-inflammation and anti-apoptosis

Abstract: Excessive inflammation and apoptosis contribute to the pathogenesis of ischemic stroke. MFG-E8 is a 66-kDa glycoprotein that has shown tissue protection in various models of organ injury. However, the potential role of MFG-E8 in cerebral ischemia has not been investigated. We found that levels of MFG-E8 protein in the brain were reduced at 24 h after cerebral ischemia. To assess the potential role of MFG-E8 in cerebral ischemia, adult male Sprague-Dawley rats were subjected to permanent middle cerebral artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 43 publications
(56 reference statements)
6
63
1
Order By: Relevance
“…These results clearly indicate that endogenous MFGE8 is required for protection against excessive postischemic cerebral damage. We also found that supplementation of WT mice ( Figure 1C) with rMFGE8 induced a significant reduction of infarct volume, in agreement with the recently reported beneficial effect of recombinant human MFGE8 in a model of cerebral injury in rats (16).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results clearly indicate that endogenous MFGE8 is required for protection against excessive postischemic cerebral damage. We also found that supplementation of WT mice ( Figure 1C) with rMFGE8 induced a significant reduction of infarct volume, in agreement with the recently reported beneficial effect of recombinant human MFGE8 in a model of cerebral injury in rats (16).…”
Section: Resultssupporting
confidence: 91%
“…MFGE8 expression has been associated with antiinflammatory effects in settings such as postischemic injury (16)(17)(18), experimental colitis (19), or sepsis (20). However, no particular antiinflammatory mechanism was identified, and the effects were indirectly related to the known role of MFGE8 in the clearance of apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the human form of MFG-E8 may be less potent in the mouse, as the homology between human and mouse MGF-E8 is only 56%. Nevertheless, rhMFG-E8 is clearly active in rodents, as we have demonstrated previously [31][32][33][34][35] and in the present study. Therefore, rhMFG-E8 is expected to have comparable beneficial effects in humans with IBD.…”
Section: Discussionsupporting
confidence: 88%
“…[31][32][33][34][35] We have injected mice with up to 2560 μg/kg rhMFG-E8 intravenously, and observed no alteration in liver transaminases (AST and ALT) 24 h later (unpublished observations). More comprehensive studies, however, will need to be conducted to exclude any toxicity.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, a recent report indicates that recombinant lactadherin may attenuate sepsis-induced apoptosis. 103 Lactadherin interacts with damaged intestinal epithelium in vivo and plays an important role in stimulating growth of intestinal epithelial cells in vitro. 104 Thus, orally ingested lactadherin could have potential in the prevention and treatment of intestinal injury in infants.…”
Section: Lactadherinmentioning
confidence: 99%